Influence of Organo-Montmorillonite on Electrical Tree Parameters in Epoxy Resin Under Ac Ramp Voltage - Mohd Hafiez Izzwan, Bin Saad; Mohd Hafizi, Bin Ahmad; Yanuar Zulardiansyah, Arief; Hussein, Bin Ahmad; Mohamed Afendi, Bin Mohamed Piah (Universiti Teknologi Malaysia Press, 2013)
This paper discusses the effects of nanofiller on electrical treeing growth in polymer nanocomposites. The polymer nanocomposite consists of epoxy resin as the base polymer and organo-montmorillonite as the nanofiller. The influence of this nanofiller on the electrical treeing breakdown resistance was investigated experimentally. The quantity of organo-montmorillonite were added in epoxy resin by ultrasonication method based on weight percentage (wt%). The weight percentages used in this experiment were 0 wt% and 1 wt%, respectively. All the samples were produced in the form of leaf-like specimens which were categorized into two parts: unfilled sample (0 wt%) and filled sample (1 wt%). Point-to-plane samples were subjected to 0.5 kVrms/s HVAC ramp voltage. The data of tree inception voltage and tree breakdown voltage were collected and comparative results were made and presented. The morphological analysis of epoxy nanocomposites were investigated using field emission scanning electron microscopy (FESEM). Electrical tree parameters analysis has shown that the existence of organo-montmorillonite in epoxy resin could exhibit significant improvement of tree characteristics of epoxy resin nanocomposites as the nanofiller contributed to the increase of tree inception voltage and tree breakdown voltage.